Palpebral Basal Cell Carcinoma Profile at Dr. M. Djamil General Hospital Padang, Indonesia - Rikha Erina; Ardizal Rahman; Mardijas Efendi (HM Publisher, 2022)
Background: Basal cell carcinoma (BCC) or basalioma is the world's most common type of non-melanoma skin cancer. 80% of BCC occurs in the head and neck area, and 20% occurs in the palpebrals. BCC contributes to 90-95% of malignancies that occur in the palpebrals, is more common in males, and the incidence is higher in those over 60 years of age. BCC grows slowly (slow-growing) and rarely metastasizes but can cause local destruction of surrounding structures. This study aims to explore the profile of palpebral basal cell carcinoma at Dr. M. Djamil General Hospital Padang, Indonesia. Methods: This study is a descriptive observational study. A total of 36 research subjects participated in this study. Data analysis was performed using SPSS univariately. Results: Palpebral basal cell carcinoma most often occurs in the age group of 61-70 years. Gender predilection is more common in men than women and generally occurs unilaterally. More people work outdoors than indoors. The inferior palpebral is the predilection for most tumor sites, and tumor invasion is found in the orbital area in 30.56% of cases. Wide excision and palpebral reconstruction are the most common treatment options. Conclusion: Basal cell carcinoma of the lids most often occurs in the age group of 61-70 years, gender of male, unilateral, more working outdoors, the most predilection in the inferior palpebral and tumor invasion is found in the orbital area in 30.56% of cases, The most common treatments are wide excision and palpebral reconstruction.